The foreign exchange market of London : development since 1900 - Atkin, John (London ; New York : Routledge, 2005)
"Foreign exchange is big business in the City of London. At the start of the twenty-first century, turnover on the London foreign exchange market averaged a staggering $504 billion a day." "It has not always been so. A hundred years ago, the London foreign exchange market played second fiddle to more important centres in New York, Paris and Berlin. This illuminating volume tells the history of this successful market in detail for the first time, examining the factors that led to the transformation of London's foreign exchange market from a backwater into the world's pre-eminent currency trading centre. An assessment is made of the contributions made by the key players, including banks, brokers and the Bank of England."
Simultaneously published in the USA and Canada.
Includes bibliographical references and index.
osc 26/06/16
Loans
Keywords: Foreign exchange market; England - London